2017
DOI: 10.4049/jimmunol.1700289
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor Activation Suppresses EBF1 and PAX5 and Impairs Human B Lymphopoiesis

Abstract: Aryl hydrocarbon receptor (AHR) is a ligand-activated transcription factor that mediates biological responses to endogenous and environmental chemical cues. Increasing evidence shows that the AHR plays physiological roles in regulating development, homeostasis and function of a variety of cell lineages in the immune system. However, the role of AHR in human B cell development has not been investigated. Toward this end, an in vitro feeder-free human B cell developmental model system was employed using human cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 59 publications
0
23
1
Order By: Relevance
“…This points to the importance of the modular promoter set-up as a basis for cell-specific usage of the AHR as we have suggested before [52]. For instance, the group of Kaminski recently demonstrated that binding of AHR to the early B cell factor 1 (EBF1) promoter results in the down-regulated expression of this B cell-specific differentiation factor [53]. In our present study, we identified 144 genes, which were up-regulated in DETC of Ahr -/mice, i.e., AHR-presence would impair their expression.…”
Section: Discussionmentioning
confidence: 81%
“…This points to the importance of the modular promoter set-up as a basis for cell-specific usage of the AHR as we have suggested before [52]. For instance, the group of Kaminski recently demonstrated that binding of AHR to the early B cell factor 1 (EBF1) promoter results in the down-regulated expression of this B cell-specific differentiation factor [53]. In our present study, we identified 144 genes, which were up-regulated in DETC of Ahr -/mice, i.e., AHR-presence would impair their expression.…”
Section: Discussionmentioning
confidence: 81%
“…Meanwhile, AhR induction inhibits the formation of early B cells and pro-B cells. AhR controls B cell differentiation by transcriptionally suppressing the early B cell genes EBF1 and PAX5 [121].…”
Section: Ahr and B Cellsmentioning
confidence: 99%
“…In the rat model this activity was found to be mediated by pro-inflammatory cytokines, IFNγ and TNFα in particular (Gardner et al, 2013). Intriguingly, data from Lisak et al (2012) suggest yet another mechanism, namely that oligodendrocyte death may be induced by B-cell-derived large molecular factors (Lisak et al, 2012), probably even extracellular vesicles (poster at American Academy of Neurology 2017 meeting; see https://www.youtube.com/watch? v=-3k1ubpq0Zo, last access: 17 April 2019).…”
Section: B Cells In Progressive Msmentioning
confidence: 99%